Protective Effect of Melatonin Against Malathion Induced Alterations in Antioxidant Defense System and Morphology of Erythrocytes in Wistar Rats - G.K. Bhatti,; I.P.S. Sidhu,; J.S. Bhatti, (Journal of Basic & Applied Sciences, 2021)
Malathion intoxication has been shown to produce oxidative stress due to the generation of free radicals and alter the antioxidant defense system in erythrocytes. Previous studies have shown the ameliorative role melatonin against oxidative stress induced by generation of free radicals. Present study was designed to investigate the protective effect of melatonin against malathion induced oxidative stress. For this purpose, male Wistar rats were randomly divided into four groups: Control; Melatonin (10mg/Kg body weight) group; Malathion (250mg/Kg body weight) treated group; Malathion + Melatonin treated group. Animals were administered an acute dose of malathion orally. The result of this study shows that in vivo administration of malathion caused inhibition in AChE activity in erythrocytes. Malathion intoxication also significantly increased the oxidative damage as evidenced by increased level of LPO and GSH content. The Inhibition of GSH level and increased lipid peroxidation in erythrocytes was relieved in malathion + melatonin group. Enhanced activities of SOD, CAT, GR and GPx were observed in erythrocytes of malathion treated rats as compared to control group. Moreover, melatonin supplementation in malathion treated rats maintain normal level of antioxidant enzymes as compared to malathion treated rats which indicates that melatonin provide protection against malathion-induced oxidative stress in erythrocytes. No significant change in the membrane bound enzymes such as Na+/K+-ATPase, Mg2+-ATPase and Ca2+-ATPase was observed in malathion intoxicated rats. Findings of scanning electron micrographs of erythrocytes revealed that both the malathion treated and malathion+melatonin treated groups exhibited morphological changes in erythrocytes. However, concomitant melatonin supplementation normalized the morphological alterations in erythrocytes induced by malathion toxicity. In conclusion, melatonin supplementation may ameliorate malathion-induced oxidative imbalance by enhancing the glutathione level, reducing lipid peroxidation and normalizing antioxidant enzyme activities in erythrocytes.